Histone H3 lysine 36 methylation affects temperature-induced alternative splicing and flowering in plants - Pajoro, A. (Genome Biol, 2017)
BACKGROUND: Global warming severely affects flowering time and reproductive success of plants. Alternative splicing of pre-messenger RNA (mRNA) is an important mechanism underlying ambient temperature-controlled responses in plants, yet its regulation is poorly understood. An increase in temperature promotes changes in plant morphology as well as the transition from the vegetative to the reproductive phase in Arabidopsis thaliana via changes in splicing of key regulatory genes. Here we investigate whether a particular histone modification affects ambient temperature-induced alternative splicing and flowering time. RESULTS: We use a genome-wide approach and perform RNA-sequencing (RNA-seq) analyses and histone H3 lysine 36 tri-methylation (H3K36me3) chromatin immunoprecipitation sequencing (ChIP-seq) in plants exposed to different ambient temperatures. Analysis and comparison of these datasets reveal that temperature-induced differentially spliced genes are enriched in H3K36me3. Moreover, we find that reduction of H3K36me3 deposition causes alteration in temperature-induced alternative splicing. We also show that plants with mutations in H3K36me3 writers, eraser, or readers have altered high ambient temperature-induced flowering. CONCLUSIONS: Our results show a key role for the histone mark H3K36me3 in splicing regulation and plant plasticity to fluctuating ambient temperature. Our findings open new perspectives for the breeding of crops that can better cope with environmental changes due to climate change. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13059-017-1235-x) contains supplementary material, which is available to authorized users.